توجهات دولة ماليزيا في احلفاظ على هوية اللغة العربية وحضارتها = Malaysia’s approach to maintain the identity and the civilization of the Arabic language - Zakaria, Abd Wahab; Mohd Shamsudin, Nur Shuhada (Al-Quds Open University, 2015)

(untitled)
This study discusses the topic of maintaining the identity and the civilization of the Arabic language, which has a great significance in the lifeof the Malays. Indeed, Arabic plays a big role in the religious and cultural dimensions of the daily life of malays as they use Arabic words in areas such as worship rituals, education, trade and tourism. Arabic is also used by universities and schools in Malaysia as medium of instruction to teach Islamic studies e. g. jurisprudence, tafsir, hadith, muslim theology, or as a second or foreign language in other disciplines. Both inductive and historical methods are used in this study to investigate the role of Malaysia in maintaining this,language and how to take the possible means to preserve this language which is confirmed by the state as the language of Islamic civilization and the language of the Islamic religion. Apart from that, Arabic calligraphy is still being used as part of Malay writing system. Arabic is also linked to the cultural dimension, which has a significant in the field of language borrowing as well as its role in maintaining the political and cultural relations with the Arab worlds.